The Effect of Motivation and Transactional Leadership Style on Employee Job Satisfaction at Cable Company in Indonesia - Anastasia Cindy Jayadi; Sanny Ekawati (International Journal of Application on Economics and Business, 2023)
The purpose of this study is to determine the relationship between motivation and transactional leadership style on employee job satisfaction at a cable company in Indonesia. Ali et al. [1] and Amin et al. [2] found that transactional leadership style had insignificant effect to job satisfaction. Moreover, a study conducted by Anghelache [3] discovered that there is insignificant effect between motivation and job satisfaction. In this study, the sample size was 75 respondents who worked for a cable company in Indonesia. This study’s sampling method was purposive sampling by distributing online questionnaires in google forms. This study used SEM-PLS with Smart PLS software version 3.0.in processing the data. The findings indicated that motivation and transactional leadership styles have a positive and significant effect on employee job satisfaction at one of cable companies in Indonesia.